"Cognitive Training of Attention and Microbiome Control as Prerequisites for Human Capital Development". Issue 6 (March 2021) - Dzyuba, A V; Dzyuba, V A
Abstract: The paper discusses the role of gut microbiota control in human capital development. Using the analysis of existing literature authors suggest mutual entanglement of attention training practice and presence of certain microbiota population. Based on this conclusion recommendations for shaping future cognitive trainings is given. Authors also present a method for microbiome accounting in datasets where only dietary data is collected. Based on this approach possible association between microbiome and well-being domain of human capital is evaluated.